2010
DOI: 10.6018/ijes/2010/2/119231
|View full text |Cite
|
Sign up to set email alerts
|

The impact of computer-based feedback on students’ written work

Abstract: While research in second language writing suggests that instructor feedback can have a positive influence on students' written work, the provision of such feedback on a regular basis can be problematic, especially with larger student numbers. A number of computer programs that claim to provide both automatic computer-based holistic scores and computer-based feedback (CBF) on written work are available and therefore have the potential to deal with this issue. Criterion is one such tool that claims to be able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 24 publications
4
49
1
Order By: Relevance
“…Consequently, evidence of effectiveness began to be sought from users' experiences and outcomes. User-centric results show varied student/teacher perceptions, increased student motivation and learner autonomy, positive feedback effects, as well as enhanced understanding of errors and writing improvement (Attali, 2004;Chen & Cheng, 2008;Chung & Baker, 2003;El Ebyary & Windeatt, 2010;Elliot & Mikulas, 2004;Foltz, Laham, & Landauer, 1999;Li, Link, Ma, Yang, & Hegelheimer, 2014;Link, Dursun, Karakaya, & Hegelheimer, 2014;Rich, Schneider, & D'Brot, 2013;Schroeder, Grohe, & Pogue, 2008;Ware, 2011Ware, , 2014. Although the increasing number of studies sheds positive light on the potential of AWE, evidence accumulated to support its validity is relatively inconsistent and, hence, insufficiently informative for use in writing classrooms.…”
Section: Aes For Assessment and Awe For Instructionmentioning
confidence: 99%
“…Consequently, evidence of effectiveness began to be sought from users' experiences and outcomes. User-centric results show varied student/teacher perceptions, increased student motivation and learner autonomy, positive feedback effects, as well as enhanced understanding of errors and writing improvement (Attali, 2004;Chen & Cheng, 2008;Chung & Baker, 2003;El Ebyary & Windeatt, 2010;Elliot & Mikulas, 2004;Foltz, Laham, & Landauer, 1999;Li, Link, Ma, Yang, & Hegelheimer, 2014;Link, Dursun, Karakaya, & Hegelheimer, 2014;Rich, Schneider, & D'Brot, 2013;Schroeder, Grohe, & Pogue, 2008;Ware, 2011Ware, , 2014. Although the increasing number of studies sheds positive light on the potential of AWE, evidence accumulated to support its validity is relatively inconsistent and, hence, insufficiently informative for use in writing classrooms.…”
Section: Aes For Assessment and Awe For Instructionmentioning
confidence: 99%
“…The use of feedback mediated by electronic media has called the attention of numerous researchers in the past few years. A bulk of research studies have shown that computerdelivered feedback can be synchronous, asynchronous, self-paced, peer or instructor centered and it is suited to in or out of the classroom boundaries, both in distance learning, face-to-face education or blended learning (Seliem & Ahmed, 2009;Ebyary & Windeatt, 2010;Istifci, 2011;Hosseini, 2012;Vurdien, 2012;Lakarnchua & Wasanasomsithi, 2013;Arslan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, e-feedback offered by their peers was perceived as artificial and not as useful. Ebyary and Windeatt (2010) investigated the impact of automatic computer-based feedback in higher education using a computer program named Criterion. The authors collected data from 31 instructors and 549 Egyptian trainee EFL teachers using pre-treatment questionnaires, interviews and focus groups.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reviews of Warschauer & Ware (2006) as well as Ebyary & Windeatt (2010), Table 1 provides a detailed description of the most well-known AEE systems in terms of producing companies, software engines, targeted areas of writing assessment, statistical approaches to evaluation and types of scoring and feedback The AEE system chosen for the present study is e-rater®, the AEE platform manufactured by the Educational testing Service (ETS) that provides formative feedback along with an automated holistic score. This system's automated scoring application has been used for the TOEFL IBT as an independent rater for the purpose of scoring the writing independent writing task (see Enright & Quinlan, 2008 for the use of the e-rater® system in the TOEFL IBT independent writing task).…”
Section: Automated Essay Evaluationmentioning
confidence: 99%
“…Students who received constant feedback demonstrated reduced errors in grammar, mechanics, usage and style in their final drafts. Ebyary & Windeatt (2010) applied questionnaires, interviews, and focus groups to investigate the effects of using the Criterion® systems with 549 Egyptian trainees and EFL instructors. The investigation focused on attitudes towards using the Criterion® system and whether there was a noticeable influence on the writing strategies used by students.…”
Section: Automated Essay Evaluation and Writing Improvementmentioning
confidence: 99%